Megacolon due to Chronic Schistosomiasis: A Case Report and Review of Literature - Amer R. Alzahrani; Homoud Alawfi; Sara Almeman; Thamer Altayeb; Hasan M. Al-Dorzi (Case Reports in Surgery)
Although Schistosoma infection in humans commonly involves the intestines, megacolon is a rare finding. We report a 47-year-old patient who was found to have chronic megacolon. After failing conservative management, he underwent extended hemicolectomy with colorectal anastomosis. The colon pathology revealed chronic schistosomiasis and Schistosoma serology was positive.